Molecular genetics of papillary thyroid carcinoma: great expectations... - Trovisco,Vítor (2007)
Papillary thyroid carcinoma (PTC) is the most prevalent type of endocrine cancer and, in recent epidemiological surveys, one of the types of human cancer whose incidence is growing. Despite the favourable outcome and long survival rates of most patients, some tumours display an aggressive behaviour and may progress to the highly aggressive and lethal, anaplastic thyroid carcinoma. In recent years, several progresses have been made on the molecular characterization of PTC, in general, and in the genetic alterations underlying the histotype diversity of this type of cancer, in particular. This holds true regarding alterations on nuclear DNA as well as mitochondrial DNA. In this review we have summarized the most recent findings in the genetic characterization of PTC, giving a particular emphasis to the genotype-phenotype associations, the prognosis implications, and the diagnostic and therapeutic value of the newly identified genetic markers.